REKONSTRUKSI EPISTEMOLOGI STUDI ISLAM (Usaha Pengembangan Pendekatan Studi Islam di Jurusan PAI Fakultas Tarbiyah UIN Malang) - Moh Padil (lp2m-uin malang, 2006)
Modern word in inpported by modernized science and technology with in cultural and multireligius society, so for, Islamic studies uses theological approach with characters truth claem ( truth monopoly). According to this approach, the believer of certain religious is the only truth, where are other's belief is wrong. Tis appoach is not relevant anymore and can not face the challenge of this era ; then the mew way laurges from the mind of many moslem schoolars, Harun Nasution offers rational appoach, M Amin Abdullah proposes historical empirical approach, M Atho' Mudzar claem sosiological approach and Jalaluddin Rahmat present humanistic approach. The above approach can be cathegorized into theological approach, and comparative approach, stating from M Dhavamony theory, several Islamic studies approaches can be development of this approach is phenomenological approach. The Islamic studies approach focuses on sacrality and profan. So for sacrality in only strudied using the teological approach and profan in studied using philosophical approach.Keywords: Islamic studies, approach, theological approach, philosopical approach, phenomenological approach